If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6y + -1) + -1(8y + -6) = 0 Reorder the terms: 3(-1 + 6y) + -1(8y + -6) = 0 (-1 * 3 + 6y * 3) + -1(8y + -6) = 0 (-3 + 18y) + -1(8y + -6) = 0 Reorder the terms: -3 + 18y + -1(-6 + 8y) = 0 -3 + 18y + (-6 * -1 + 8y * -1) = 0 -3 + 18y + (6 + -8y) = 0 Reorder the terms: -3 + 6 + 18y + -8y = 0 Combine like terms: -3 + 6 = 3 3 + 18y + -8y = 0 Combine like terms: 18y + -8y = 10y 3 + 10y = 0 Solving 3 + 10y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 10y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 10y = 0 + -3 10y = 0 + -3 Combine like terms: 0 + -3 = -3 10y = -3 Divide each side by '10'. y = -0.3 Simplifying y = -0.3
| (11n+3)(2n-5)=0 | | -39-x=4x+71 | | 32.54m=292.86 | | -12-3x=-4x+8 | | 12x^2-25x+2=0 | | 8*3(3+2)-6= | | 2.5x=15.2 | | -94-2x=5x+32 | | x^2-7=-y^2+6y | | 0.11x+0.1(6000-x)= | | 32x+3=2 | | -30+7x=25+2x | | 60x=35+150 | | 18s^2-11s+1=0 | | 8x-64=-5x+144 | | sin(a)=0.5 | | 10y-28+8y+4= | | -69+6x=-3x+66 | | (3/5d)+5=(1/3d)-3 | | n^2-8n=9 | | -12g=96 | | 3/5d+5=1/3d-3 | | 5y^2=-9y-1 | | n^2-18n+80=0 | | -0.2x+8=0.5x-10 | | 6m+2=m+13 | | 4k+5=-3k-2 | | -72+7x=84-5x | | (1*8*3)=4*x | | 2g=96 | | 12.45=9.15x+x | | 9x-85=-x+65 |